2015
DOI: 10.1155/2015/901983
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Induces Apoptosis in Liver Cells through Induction of ROS

Abstract: Oxidative stress mechanisms are involved in hepatotoxicity. The liver is reported to be affected by bisphenol A (BPA) in animals studies and has been also reported to possess hepatic toxicity. This study aimed to examine association between liver health status and the effects of BPA on the antioxidant defense systems and liver biomarkers. BPA (0, 2, 10, and 50 mg/kg) body weight was mixed in corn oil and intraperitoneally administered every forty-eight hours for 30 days in dose-dependent manner. There was no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 44 publications
4
27
0
1
Order By: Relevance
“…Another explanation could be the fact that BPA-induced liver damage was so severe that corn oil coadministration failed to reduce such damage to approach the control group. In concordance, previous studies indicated BPA induced deleterious effects on the liver and other organs even it was dissolved in corn oil (El Ghazzawy et al 2011;Yıldız & Barlas 2013;Kourouma et al 2015;Kazemi et al 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another explanation could be the fact that BPA-induced liver damage was so severe that corn oil coadministration failed to reduce such damage to approach the control group. In concordance, previous studies indicated BPA induced deleterious effects on the liver and other organs even it was dissolved in corn oil (El Ghazzawy et al 2011;Yıldız & Barlas 2013;Kourouma et al 2015;Kazemi et al 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Because GSH is an important cofactor for GPx activity (Huang et al 2004), reduction in hepatic GSH content here may reduce GPx activity enhancing oxidative stress. This may be attributed to BPA-induced oxidative damage to the liver releasing hepatic enzymes into the blood or to hyperactivity of the liver (Kourouma et al 2015). Thus, exposure to BPA in the current study might increase the activity of GST to help in the detoxification of BPA and degradation of lipid peroxides at the expense of GSH content that participates in the catalytic activity of GST.…”
Section: Inflammatory Markersmentioning
confidence: 83%
See 1 more Smart Citation
“…In agreement to our results, a significant increase in the serum MDA level were found in rats exposed to BPA compared to the control group [16] . Also, study of Kourouma et al [17] showed exposure of rats to BPA resulted in significant increase of liver MDA level. Several studies [2,3,12,13,18,19] demonstrated that exposure to BPA generate reactive oxygen species, but reduce antioxidant content and activity.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have proposed that the increase in lipid peroxidation is directly proportional to that of LDH activity (Hrelia et al, 2002) in the extracellular fluid, hence indicating myocardial cell membrane damage. Elevation of LDH activity usually denotes irreversible cardiomyocyte injury (Kourouma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%